Deep-Dive on Malaysia’s Higher Education Services Trade : March 2022 - World Bank (Washington, DC, 2022)
Malaysia’s higher education sector expanded rapidly in the late 1990s, with the number of institutions peaking in 2001 and the number of international students peaking in 2017. Following improvements in the quality of local universities and the establishment of branches of international campuses in Malaysia, the country has become a net receiver of foreign students. Enhanced trade in the higher education sector, and the expansion of the sector, bodes well for Malaysia’s next phase of economic development. The objectives of this paper are to document the pattern of trade in higher education services in Malaysia and to analyze the main factors that constrain trade in this sector. First, the paper aims to document Malaysia’s higher education landscape and the pattern of trade in each of the four modes of services trade. Second, it seeks to identify key policy challenges and constraints affecting this sector. The paper employs a combination of quantitative, qualitative, and institutional research methods. The paper finds that despite numerous liberalization measures, a number of remaining restrictions and limitations continue to impact trade in the sector. The paper finds that the most significant policy challenges likely relate to domestic constraints. To attract foreign students and faculty members and to enhance trade in the higher education sector, it is crucial to ease the visa and immigration processes and rules. Furthermore, measures to enhance the digitalization of administrative processes at the regulatory agencies and at Higher Education Institution (HEIs) can increase efficiency, with the potential to reduce the burden associated with excessive documentation requirements. It is also crucial that agencies and universities systematically collect more data to better inform policy reforms and guide universities in how to improve their programs.